2016
DOI: 10.3390/su8050457
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Evolvement of Technology Development and Energy Efficiency—A Case Study of the Past 30 Years of Development in Shanghai

Abstract: Previous research in regional energy efficiency by using macro statistical data has demonstrated that technology development could improve regional energy efficiency. Since the start of reform and opening up in 1978, China has mainly adopted energy import and foreign direct investment to promote economic growth. At the same time, the country has also increased the input of technology and R&D to prompt technological reformation and imported technology absorption. However, there is limited research on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Zhang et al (2017) indicated that the economic contribution of R&D could boost the application for environmental patents, improve energy efficiency, and achieve a reduction in CO 2 emissions. Wei et al (2016) concluded that technological reformation and R&D could promote regional energy utilization efficiency and decrease CO 2 in Shanghai. Tamazian et al (2009) believed that supporting investment in the R&D of energy-efficient technologies in Brazil, Russia, India, China and South Africa (BRICS) countries might promote technological innovation, which might aid in emission reduction efforts.…”
Section: Technological Progress and Co 2 Emissionsmentioning
confidence: 99%
“…Zhang et al (2017) indicated that the economic contribution of R&D could boost the application for environmental patents, improve energy efficiency, and achieve a reduction in CO 2 emissions. Wei et al (2016) concluded that technological reformation and R&D could promote regional energy utilization efficiency and decrease CO 2 in Shanghai. Tamazian et al (2009) believed that supporting investment in the R&D of energy-efficient technologies in Brazil, Russia, India, China and South Africa (BRICS) countries might promote technological innovation, which might aid in emission reduction efforts.…”
Section: Technological Progress and Co 2 Emissionsmentioning
confidence: 99%
“…On the other hand, EPD indirectly affects energy efficiency by affecting technological innovation and energy consumption structure [7]. Technological innovation is one of the most effective ways to improve energy efficiency [44]. EPD means that lower costs are input for enterprises to obtain production materials, which reduces the enthusiasm of producers to carry out technological research and development.…”
Section: Estimating the Impacts Of Energy Price Distortionmentioning
confidence: 99%
“…Some scholars show that the technological development can improve regional energy efficiency in the longitudinal case study (Wei et al 2016); however, in the global context, the effect of technological efficiency on energy intensity is not obvious.…”
Section: Effects Of Education and Technology On Energymentioning
confidence: 99%
“…Clermont (2016) revealed that the initial positive developments of effectiveness and efficiency are mainly due to technology advances, whereas the following decreases are basically a result of technology backwardness. Wei et al (2016) pointed out that a country has also increased the input of technology and R&D to prompt technological reformation and imported technology absorption. Park (2014) analyzed the efficiency of small-and medium-sized enterprises of a national technology innovation R&D program.…”
Section: Literature Reviewmentioning
confidence: 99%